1993
DOI: 10.1073/pnas.90.7.2865
|View full text |Cite
|
Sign up to set email alerts
|

Bovine papilloma virus (BPV)-encoded E2 protein enhances binding of E1 protein to the BPV replication origin.

Abstract: The replication of bovine papilloma virus (BPV) DNA in vivo requires two viral-encoded proteins, El and E2, while all other proteins are derived from the host. We described previously the isolation of the El protein and showed that it contains multiple functions required for BPV DNA replication. The BPV transcription factor E2 was shown by others to stimulate BPV DNA replication in vitro. Here, we present results that account for the role of the E2 protein. The El protein bound selectively to the BPV minimal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(163 citation statements)
references
References 21 publications
(18 reference statements)
9
151
3
Order By: Relevance
“…Purified E1 protein can initiate in vitro viral replication without the support of the E2 protein (6). However, the interaction of E1 with E2 protein promotes specific binding and assembly of E1 protein on the viral origin to form an active initiation complex (7,8). Additional functions of E1 include recruiting cellular replication factors, such as the DNA polymerase ␣ and replication protein A (9 -11).…”
Section: Bovine Papillomavirus (Bpv)mentioning
confidence: 99%
“…Purified E1 protein can initiate in vitro viral replication without the support of the E2 protein (6). However, the interaction of E1 with E2 protein promotes specific binding and assembly of E1 protein on the viral origin to form an active initiation complex (7,8). Additional functions of E1 include recruiting cellular replication factors, such as the DNA polymerase ␣ and replication protein A (9 -11).…”
Section: Bovine Papillomavirus (Bpv)mentioning
confidence: 99%
“…Its role during the process of initiating DNA replication is thus unclear. By establishing a molecular association with E1 (Mohr et al, 1990;Blitz & Laimins, 1991;Lusky & Fontane, 1991), E2 has been shown to improve E1 binding to the ori (Seo et al, 1993b;Lusky et al, 1993). In addition, as suggested by recent in vitro replication experiments (Li & Botchan, 1993, acidic transcription factors could increase the efficiency of DNA replication, if appropriate binding sites are replacing the E2 responsive elements that normally are located adjacent to the ori.…”
Section: -2921 © 1995 Sgmmentioning
confidence: 99%
“…Furthermore, the efficiency of BPV 1 DNA replication has been shown to correlate with the affinity of E2 binding to its cognate sequences in the origin (22). The BPV1 E2 directly interacts with El (25)(26)(27), and this interaction leads to enhancement of El binding to its site within the core origin (25,(28)(29)(30). Hence, part of the role of E2 in BPV1 DNA replication relies on its capacity to tether El to the origin.…”
Section: Introductionmentioning
confidence: 99%